Legal Protection Of Land Ownership Rights In Coastal Areas Affected By Abrasion: Climate Change, Coastal Border Regime, and Tenure Uncertainty In Indonesia - Muhammad Addi Syirfan; D. Djunaedi; Adinda Zeranica Putri Fakhis; Laily Fadhilah Sabilal Haque (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
Global climate change, which has triggered sea level rise and extreme abrasion, now poses a real threat to the stability of property rights regimes in coastal areas. This study offers a theoretical contribution to the agrarian law discourse by analyzing the failure of the static legal paradigm in dealing with the dynamics of natural change. Focusing on the city of Pekalongan, Indonesia, this study uses a socio-legal approach that synthesizes normative analysis, empirical field data, and Geographic Information System (GIS) mapping to reveal the legal tension between property certificate holders and the designation of coastal zones. The findings show that the current legal regime suffers from acute sectoral fragmentation; on the one hand, it recognizes the existence of property rights administratively, but on the other hand, it affirms their function through ecological coastal zone policies. This inconsistency creates legal bias against coastal residents. This study argues that the current legal protection model is still inadequate and that there is an urgent need for reconstruction towards an adaptive legal framework. Although some legal protections are in place, they are still insufficient to provide legal certainty for communities and ecological justice. The international relevance of this research lies in offering solutions for island nations in managing tenure conflicts on coastlines that are constantly changing due to the global climate crisis